Blood, sweat & tears a genre study of South Korean boy groups BTS's music videos - Rosales, Clara Francesa Bactad 1998-; Olaguer-Aljibe, Ma. Amor; University of the Philippines Diliman. College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2018)
This thesis examines the music video genre. Specifically, it seeks to examine the narrative and structure present in music videos of South Korean Pop boy group BTS and has the main objective of exploring the narrative and structure of these Korean music videos to determine if they follow current music video conventions or break them. This sample of eleven music videos is selected as the music used in the music videos belong to an album series that the boy group releases in the span of a year and four months. The study utilizes Rapahelle Moine's discussion on genre, Boris Eikhenbaum's formal method, and Andrew Goodwin's music video analysis on narrative and structure. The history and the evolution of the music video is also tackled using the studies of Simon Frith, Lawrence Grossberg, and Paul Temporal, taking into consideration how Music Television (MTV) changed the landscape of music and music television consumption. BTS's music videos adhere to the conventions of television music videos while trying to keep up while being uploaded online. BTS introduces a new type of storytelling that gives each music video its own narrative, and links it to other music videos in order to create an overarching narrative.
Vita.
Thesis (A. B. Broadcast Communication)--University of the Philippines Diliman
Includes bibliographical references.
Keywords: Music videos -- Korea; BTS -- Musical groups; K-Pop.